Antifungal Activity of Piper Betle Leaf: Exploring the Potential of Piper Betle Leaf as a Novel Antifungal Agent (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mycosis is a widespread health issue, especially in the tropical and subtropical developing countries; dermatophytes, species Malassezia and species Candida are the most common pathogens in humans and animals. There has been a growing search for new antifungal agents in recent years. However, as many of the current antifungal medications have adverse side effects or are extremely toxic (amphotericin B), induce recurrence, demonstrate drug-drug interactions (azoles) or contribute to resistance production (fluconazole, 5- flucytosine), others display ineffectiveness and have thus been less active in therapeutic strategies.Therefore, more powerful and less toxic novel antifungal agents need to be looked to address these drawbacks. It is important to note that plants are commonly used in folk medicine, especially in communities with insufficient public health and sanitation conditions.